MODIFICATION OF POLYTETRAFLUOROETHYLENE ON THE BASE OF ULTRAFINE POWDER - Tlebaev, K.B.; Kurmanbaeva, G.A. (KU Publ., 2021)
This paper presents the results of a study of the influence of thermal and mechanical effects on the formation of a structure in an ultrafine powder heated to a temperature above the melting point of polytetrafluoroethylene (327°C). The ultrafine powder was obtained by mechanical grinding of an industrial sample of polytetrafluoroethylene in a rotary knife mill. Studies of the ultra powder with a transmission microscope showed that the powder particles are quasi-spherical particles of a size of 5 microns. The thermal (sintering, slow and fast quenching) and mechanical (creation of high pressure) effects on ultrafine powder particles were determined by the methods of an automated digital microscope Leica DM 6000, X-ray diffraction, and Vickers. It was found that the formation of a supramolecular structure depends on the applied force (pressure) and temperature. Measurement of the hardness of the modified sample showed that its hardness in relation to the hardness of the industrial sample increased by 4 units.
Keywords: polytetrafluoroethylene; modification; ultrafine powder; supramolecular structure; thermal and mechanical effects